Testing and isolation strategies for the vibrational hazards - Wei, Huang (Array, 2019)
In this paper, a test for investigating the vibrational hazards occurred in a modernized hospital was carried out, in which a lot of power equipment such as chilled water pumps and freezers, etc. were installed in the ground floor. The generated vibrations could be experienced on the upper floors including some medical precision room. Next, solation and active control strategies were proposed, and evidently the active control could improve the suppression a lot. This study illustrated that the great vibrational hazards could not be ignored anymore, and the followed resolution strategies for eliminating these vibrations seemed to be urgent. In tradition, the vibration isolations would not be involved in initial design for civil structures, but in fact this might lead to a severe problem to be addressed in the future, and this study could give inspiration for green building.